Development Policy under Fire? The Politicization of European External Relations*. (31st January 2021) - Hackenesch, Christine; Bergmann, Julian; Orbie, Jan
Abstract: In the past few years decision‐making processes and the normative underpinnings of EU external relations have become subject to intense debate in the European institutions, member states and the wider public. Previous research suggests that there is variation in the extent to which individual domains of EU external relations are politicized and contested. This special issue aims to theorize further and investigate empirically this, using the example of European development policy and its relations with other external policies. We introduce two new mechanisms that drive politicization dynamics. We argue that politicization can be diffused horizontally from one policy field to another, which we call horizontal politicization. We also investigate how the politicization of EU external policies in third countries occurs and influences politicization dynamics in the EU, which we call outside‐in politicization. The introduction to the special issue presents our theoretical approach and summarizes the key findings from the special issue.